2010
DOI: 10.1002/ppul.21184
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection outbreak among pediatric patients with oncologic diseases and/or BMT

Abstract: In contrast with the outcome of RSV infection in adult oncology patients, the mortality associated with RSV infection in pediatric oncology patients even in post bone marrow transplantation (BMT) period, is low when diagnosed and treated early enough. Oral ribavirin might be an option together with IVIG in the treatment of RSV especially when other forms of antivirals could not be obtained. This approach will make it possible to give the scheduled anti-neoplastic therapy on time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 21 publications
1
38
0
3
Order By: Relevance
“…RSV outbreaks among vulnerable hospitalised patients are of particular concern as affected patients are more likely to experience longer hospital stays, with increased risk of morbidity and mortality 4, 7, 8. Numerous hospital outbreaks have been reported in multiple age groups and settings including neonatal intensive care, haematology, transplant and oncology units 9, 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…RSV outbreaks among vulnerable hospitalised patients are of particular concern as affected patients are more likely to experience longer hospital stays, with increased risk of morbidity and mortality 4, 7, 8. Numerous hospital outbreaks have been reported in multiple age groups and settings including neonatal intensive care, haematology, transplant and oncology units 9, 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…Additional therapies, including intravenous immunoglobulin (IVIG), RSV hyperimmunoglobulin, and palivizumab (a monoclonal RSV IgG), have been utilized for RSV infection with mixed efficacy in immunocompromised patients [31,[49][50][51]. Early studies suggested that ribavirin plus RSV-IVIG (RespiGam/MedImmune), a hyperimmune globulin preparation with high concentrations of RSV-neutralizing antibody, conferred a mortality advantage over ribavirin alone in RSV-infected pediatric HSCT patients with LRD; however, RSV-IVIG has since been removed from the market because alternatives now exist to this human plasma-derived product (RespiGam) [52].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…However, this recommendation is not strongly supported by the American Academy of Pediatrics [53]. Palivizumab was used as prophylaxis in an adult HSCT unit following an RSV outbreak in which 16 RSV-negative patients received the drug in combination with strict infection control measures, and none acquired the virus [50]. In contrast, a case series of 40 allogeneic HSCT patients infected with RSV received treatment with palivizumab, but this did not seem to have any impact on the progression to LRD or mortality [54].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Consequently, no international consensus has been reached and pediatric patients still remain understudied. In this regard, some studies suggest improved outcomes with the addition of high-dose Ig, 18,19 RSV-IVIG 20 or MoAb (palivizumab) 21 in children undergoing HSCT, but clear evidence of efficacy is lacking. Prophylaxis with palivizumab has been approved by the FDA in prematurity or in bronchopulmonary dysplasia, 22 but is still limited by its high cost.…”
Section: Intravenous Ribavirin In Pediatric Hematopoietic Transplantamentioning
confidence: 99%
“…No RSV-specific gamma globulin or humanized MoAb (palivizumab) was administered. All four LRTI patients showed a favorable clinical response, with 100% survival after a mean follow-up of 17 months (range [13][14][15][16][17][18][19][20][21][22][23][24]. With regard to IVIG, our guideline was not adhered to in two patients with severe LRTI-RSV who did not receive combined therapy with IVIG (episodes 1 and 6).…”
Section: Patient Characteristicsmentioning
confidence: 99%